(NiZBRANNYE SO^INENIQ W DWUH TOMAH (B/s (N~ASTX (B2s - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1984)
(NwO WTOROJ TOM (B"(NiZBRANNYH SO^INENIJ(B" (Nn(B.(Nw(B.(NgOGOLQ PO[LI [EDEWRY DRAMATURGII (B"(NrEWIZOR(B", "(NvENITXBA(B", "(NiGROKI(B" (NI WER[INA TWOR^ESTWA PISATELQ PO\MA (B"(NmERTWYE DU[I(B", (NOTRAZIW[AQ WSE MNOGOOBRAZIE RUSSKOJ VIZNI NA^ALA PRO[LOGO WEKA(B.s
rus
Keywords: (NsATIRA(B, (N@MORs; (NrUSSKAQ LITERATURAs